Adding 212121 to both sides of the equation, we get:
y^7 − 3 + 212121 = 39 + 212121
Simplifying, we have:
y^7 + 212118 = 212160
Next, multiplying no response given to both sides of the equation, we get:
no response given * (y^7 + 212118) = no response given * 212160
This simplifies to:
no response given * y^7 + no response given * 212118 = no response given * 212160
Beejal is solving the equation y7 − 3 = 39 .(1 point)
As a first step, he starts by adding 212121 - incorrect to both sides of the equation, and then continues by multiplying by no response given on each side.
1 answer